PENGETAHUAN IBU TENTANG PENCEGAHAN INFEKSI COVID-19 PADA SAAT POSYANDU DI DESA KWALA BINGEI - Aritonang, Juneris; Siregar, Laura M; Saragih, Frida Liharris; Argaheni, Niken Bayu (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Posyandu services were stopped during the Covid-19 pandemic, posyandu services were carried out independently with the implementation model being handed over to each region according to the conditions or covid zone of each region. The implementation of the posyandu must strictly comply with established health protocols to minimize the risk of Covid-19 transmission. The initial survey conducted found that mothers were still worried about bringing their children to the posyandu. In addition, it was also found that at the time of implementing the posyandu there were still mothers who had not complied with the health protocols. This research is a descriptive study which aims to see the knowledge of mothers about the prevention of Covid-19 infection at the posyandu in Desa Kwala Bingei in 2020. The population of this study is all mothers who have toddlers and carry out posyandu with a total sample of 37 people. The results of the study found that the majority of respondents had less knowledge (65%) about the prevention of Covid-19 infection at the time of implementing the posyandu. From the results of this study, an activity in the form of health education to groups of mothers who have toddlers is needed which is related to increasing knowledge in preventing Covid-19 infection during the posyandu period, thereby reducing maternal anxiety of carrying posyandu children and posyandu activities to continue running smoothly according to health protocols.